Doing your undergraduate social science dissertation [ - Smith, Karen; Todd, Malcolm J.; Waldman, Julia (Routledge, 2009)
Using a mixture of useful information, exercises, practical strategies, case study material and further reading, it helps you through the process, giving hints and tips on beginning and managing your research project and working with your supervisors.